Abducens Nerve Palsy as Initial Manifestation of Chronic Subdural Hematoma: Case Report - Magalhães, Marcelo José Silva; Oliva, Henrique Nunes Pereira; Pereira, Getúlio Paixão; Ramos, Lucas Gabriel Quadros; Azevedo, Henrique Caires Souza (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2019)
Chronic subdural hematoma (CSDH) is a form of progressive intracranial hemorrhage, typically associated with cases of trauma. The manifestation of this comorbidity with abducens palsy is a rare finding. The present work aims to describe the case of an adult patient with abducens nerve palsy as a manifestation of CSDH. Chronic subdural hematoma is most commonly found in elderly patients, with systemic hypertension as a manifestation. The relation with the sixth cranial nerve is unusual and draws attention to the case reported. In addition, the prognosis is positive, since trepanation and drainage surgery was performed, as it is recommended in the literature.
Keywords: chronic subdural hematoma; abducens nerve palsy; cranioencephalic trauma